Exposure to Live in Geographically Steep Terrain Decreases_x000D_ Patella Height and Increases the Incidence of Patella Baja - AKDENİZ, ESRA (My University, 2020)
Objectives: This study aims to investigate the effect of the geographical conditions on patellar height.Methods: Two different groups of the same society were created according to the geographical structures that peoplelive in (fully rugged mountainous terrain Giresun and flat terrain Alanya). But the daily activities such as kneeling, praying,squatting or sitting with crossed legs were same culturally. The study included patients living and working in theseareas, as their parents, throughout their lives. Knee MRI of patients who did not suffer anterior knee pain were retrospectivelyevaluated. The Insall-Salvati index (ISI) was calculated and the patella baja incidence rates were comparedbetween regions using the Fisher’s exact test.Results: A total of 885 knee MRIs were evaluated. The mean ISI for all individuals was found significantly different witha mean of 0.946±0.141 in Giresun and 1.014±0.13 in Alanya (p<0.001). The incidence of patella baja for all individualswas 5% in Giresun and 2% in Alanya (p=0.01).Conclusion: Our findings suggested that as the inclination of the region gets steeper; the patella height decreases andthe patella baja incidence rate increases. Living in steep sloped geographical structures may be relevant in the etiologyof patella baja.